Możliwości zastosowania technologii radiowej w identyfikacji produktów w systemie informacyjnym logistyki - Leszczyńska, Maja (Implementing Radio Frequency Identification in Logistic Information Systems, 2007)
The supply chain is a complex multi-stage process which involves everything from the procurement of raw materials used to develop products and their delivery to customers via warehouses and distribution centers. The Logistic Information System allows companies involved in this chain to supervise information about products as they move through the different processes. Nowadays companies have to operate and adopt to very fast changing circumstances. So they have to get information as fast as possible. Implementing radio frequency identification helps them to achieve this goal. It is a method of identifying unique items using radio waves. This article presents the concept of implementing RFID in Logistic Information Systems. The author is also attempting at characterizing the radio frequency identification.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 115-127